Perlindungan Hukum Bagi Anak Yang Dijadikan Kurir Tindak Pidana Narkotika - Roy Aron Tampubulon; Siregar, Rospita Adelina (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Children have an important role in social and state life, because of their position as the nation’s successors. Therefore, children have the potential to play an active role in preserving the life of the nation, in order to realize the goal of establishing a government that protects citizens. Narcotics abuse by children is currently a concern for many people and is continuously discussed and publicized. In fact, the problem of narcotics abuse is of concern to various groups, especially the involvement of children as narcotics couriers, which is a series of evil conspiracy to carry out illegal narcotics distribution. In the capacity of a child being used as a courier, it is a very worrying thing where the child will face the law and be classified as having committed a narcotics crime. With children’s limited abilities and imperfections, it is necessary to pay attention to law enforcement officials in implementing punishment for children who are perpetrators of narcotics crimes. This research is normative legal research with a statutory approach, analytical approach. The type of data used is secondary data: Law Number 35 of 2009 concerning Narcotics, Law Number 35 of 2014 Amendment to Law Number 23 of 2002 concerning Child Protection, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Criminal Code, while secondary legal materials are obtained from law books and other literature, tertiary legal materials are in the form of dictionaries.